A Study on Factors that Affect School Enrolment and Dropout Rates - Verma, Megha; Yadav, Chhavi (Journal of Commerce and Trade, 2015)
Education is an affective instrument for social and economic development of society. Education is an affective instrument for social and economic development and national integration. It contributes not only for the development of human resources and efficacy. The main reason for this study, One is educational attainment among Schedule Caste and Schedule Tribes in comparatively lower than the general population. The wide gap in educational attainment between the SCs/ STs and the rest of the population is due to the long history of their socio economics explosion and low social and physical and some local factors. Basically the extreme poverty is most Dalit familiars live in underlying reason why dropout rate of Dalit children is so high. Status rate means the proportion of all individuals in the population who have not completed high school and were not enrolled at student has been dropped in VI to X class.